Column diameter dependence of the strain relaxation effect in GaN/AlGaN quantum wells on GaN nanocolumn arrays. (11th November 2019) - Oto, Takao; Mizuno, Yutaro; Yamano, Koji; Yoshida, Jun; Kishino, Katsumi
Abstract: We experimentally demonstrated the strain relaxation effect in uniform GaN/Al0.19 Ga0.81 N quantum wells on GaN nanocolumn (NC) arrays with various column diameters and periods created using the Ti-mask selective area growth technique. The photoluminescence (PL) emission from the GaN well layer was not affected by the period of the NC arrays. As the column diameter decreased, the PL peak energy of the GaN well layer blueshifted, whereas that of the GaN NC underlayer remained almost unchanged. This blueshift was reproduced with the calculated strain relaxation effect, indicating that the strain in the GaN well layer decreased as the column diameter decreased.